A faltering origin for the Acheulean? Technological and cognitive implications from FLK West (Olduvai Gorge, Tanzania). (20th August 2019) - Diez-Martín, F.; Wynn, T.; Sánchez-Yustos, P.; Duque, J.; Fraile, C.; de Francisco, S.; Uribelarrea, D.; Mabulla, A.; Baquedano, E.; Domínguez-Rodrigo, M.
Abstract: The discovery in FLK West lowermost level 6 (Olduvai Gorge, Tanzania) of a massive and symmetrical handaxe, at odds both with the other LCT specimens so far unearthed from this site and with the technological traits commonly reported for the earliest Acheulean ca. 1.7 Ma, challenges the hypothesis of a gradual development of technological and cognitive qualities during the Acheulean. This thought-provoking specimen points to a less sharp difference between the first and later phases of the Early Acheulean (i.e. between ca. 1.7 and 1.2 Ma) and supports a somewhat punctuated flourishing of the handaxe technical and cognitive conceptualization. In this regard, this paper provides a detailed descriptive study of the large olivine basalt handaxe, in the framework of both the FLK West L6 lithic collection and the LCT shaping strategies. This analysis includes a morphometric description of the specimen and a comprehensive analysis of the knapping and shaping sequencing, through a diacritical study. It also includes a techno-functional assessment of the final design and symmetry. Finally, this paper examines some of the most significant implications of this large tool for our current views on temporal divisions within the African Acheulean and the cognitive abilities of the individual that made it. Highlights: This paper deals with the technological and cognitive implications of an sceptional handaxes recovered from one of the oldest Acheulean sites in Africa. The specimen is studied both in detail (an option that we consider useful for the audience) and in a broader FLK West context. The characteristics of this specimen can bear significant implications in the way we understand gradualism in tool conceptualization during the Acheulean techno-complex.